Soft Robotic Deployable Origami Actuators for Neurosurgical Brain Retraction - Amadeo, Tomas; Van Lewen, Daniel; Janke, Taylor; Ranzani, Tommaso; Devaiah, Anand; Upadhyay, Urvashi; Russo, Sheila (Frontiers in Robotics and AI, 2022)
Metallic tools such as graspers, forceps, spatulas, and clamps have been used in proximity to delicate neurological tissue and the risk of damage to this tissue is a primary concern for neurosurgeons. Novel soft robotic technologies have the opportunity to shift the design paradigm for these tools towards safer and more compliant, minimally invasive methods. Here, we present a pneumatically actuated, origami-inspired deployable brain retractor aimed at atraumatic surgical workspace generation inside the cranial cavity. We discuss clinical requirements, design, fabrication, analytical modeling, experimental characterization, and in-vitro validation of the proposed device on a brain model.